Who Cares? Exploring Student Perspectives on Care Ethics - Kelly A. Concannon Mannise (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
Care ethics are influenced by conflicts between crafted theories and how students read those theories in practice.